Morphology of graft endothelium and donor age. - Rao, G N (1980)
The corneal endothelium of 42 clear corneal transplants was studied with a specular microscope. The endothelial cell morphology was analysed by using a computerised image analysis system. A quantitative index was developed to study the degree of variation in cell size. By applying this objective index we observed that pleomorphism is independent of age, and considerable alteration occurs in cell morphology during healing.